The Roles of New Technology and the Law in the Fight Against Covid-19 - Dawie de Villiers (The Thinker)
The importance of South Africa adapting to the Fourth Industrial Revolution (4IR) has been high on the national agenda in recent years. However, the adoption of artificial intelligence (AI) and other forms of technology has been hampered to some extent by fears of job losses and privacy issues.